FEMININE HAGIOGRAPHIC. AN UNPRECEDENTED TEXT BY FREI ALEIXO DE MENESES - Gonçalves Guimarães, Jorge (2019)
Concerning the hermits of Saint Augustine, the 17th century text about Beatriz Vaz de Oliveira written by Friar Aleixo de Meneses establishes the most significant example of feminine hagiographic literature of that monastic order.